Efektifitas Psikologi Kerekayasaan Tata Ruang Kerja Terhadap Motivasi Kerja Karyawan Gravure Production di PT XYZ - Jeklin Darsono Sidebang; Arif Rahman Hakim; Regi Ramadan (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to examine the effectiveness of workplace design psychology in improving employee motivation at PT XYZ. The approach used is a quasi-experimental quantitative method with a Two-Group Pretest-Posttest design. The research sample consists of 60 employees from the gravure production division, divided into two groups: the experimental group and the control group. Data collection was conducted using a work motivation scale based on Herzberg's theory(1966). Pretest and posttest results were analyzed using the independent sample t-test and gain score test. The research findings indicate that the experimental group experienced a significant increase in work motivation after the intervention, with a t-test value of 4.040 (p < 0.001) and an effect size of 38.56%. Thus, this study proves that the application of workplace ergonomics psychology is effective in enhancing employee work motivation, thereby accepting the alternative hypothesis (Ha).